2017
DOI: 10.1186/s12884-017-1569-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iodine status during lactation and infant weight and length in Henan Province, China

Abstract: BackgroundInfants are very sensitive to iodine deficiency. Breastfed infants are dependent on maternal iodine intake. The aim of this study was to evaluate the relationship between maternal iodine status during lactation and infant weight and length.MethodsA cross-sectional survey was conducted to investigate maternal iodine status and infant anthropometric measures in Henan Province, China. Only exclusive breastfeeding mothers and their infants < 6 months of age (n = 747) were included in our final analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
(39 reference statements)
0
15
0
1
Order By: Relevance
“…To estimate the sample size, we considered the significance level and statistical power, and we estimated the ratio of the exposed to the unexposed from the results of previous studies [ 12 13 14 ]. According to a prospective study of 344 Korean pregnant women during their third trimester conducted among hospital-based participants, we calculated the ratio of the exposed to the unexposed by UIC levels [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the sample size, we considered the significance level and statistical power, and we estimated the ratio of the exposed to the unexposed from the results of previous studies [ 12 13 14 ]. According to a prospective study of 344 Korean pregnant women during their third trimester conducted among hospital-based participants, we calculated the ratio of the exposed to the unexposed by UIC levels [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Postnatal growth studies are limited in both observational and iodine supplementation intervention studies during lactation [31]. In a study performed in China by Yang, a maternal iodine deficiency based on urinary iodine levels <50 µg/L during lactation was linked to a decreased infant WFA and LFA for infants <6 months of age, with positive effects of maternal iodine status on infant weight; however, BMIC was not measured to determine infant intake [1]. A review of survey data by Mason showed a positive relationship with iodine salt use and increased infant WFA and mid-upper-arm-circumference at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine is a key micronutrient required for adequate growth and development through its critical role in thyroid hormone synthesis [1]. Deficiency in iodine during the neonatal and infant periods may result in impairments in brain development, cognitive outcomes, motor function, and growth stunting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Após o nascimento, o cérebro humano ainda está em crescimento e a maior parte do desenvolvimento desse órgão acontece antes que a criança atinja três anos de idade (PEREIRA, 2011), sendo o iodo fundamental para que isso aconteça de forma saudável. Os recém-nascidos são muito sensíveis à deficiência iódica, e após o nascimento, aqueles que estão em aleitamento materno exclusivo são dependentes da ingestão de iodo materna, sendo imprescindível que a lactante esteja com seus níveis de iodo dentro da faixa de normalidade (YANG et al, 2017b). Sabe-se que o hipotireoidismo congênito neonatal pode acarretar distúrbios graves como o cretinismo, que é o desenvolvimento de crianças com retardo mental, baixa estatura, mãos e pés edematosos e surdo-mudez (PÉON, 2015).…”
Section: Yan Et Al (2017)unclassified